A study of determinants and impacts of leading Chinese firms’ corporate social responsibility activities - Wu, Shuangqi (2020)
Being helpful and kind is a virtue rooted in Chinese culture. However, profit-making and fast-growth orientation in the Chinese business sector has caused a series of social issues. In 2008, the Sanlu milk scandal and firms’ donations to Wenchuan-earthquake relief were typical bad and good examples of socially responsible behaviors. Given social responsibility on one side and social irresponsibility on another side, this thesis has threefold objectives in response to the lack of thorough CSR studies in China and potential methodology issues. With a combination of multiple theories including stakeholder theory, institutional theory, corporate governance theories and agency theory as theoretical foundations, this thesis first applies fixed-effect models to untangle the factors determining a good level of Chinese companies’ overall social performance in the same year and a lagged year by using a sample of Chinese listed companies from 2008 to 2012. Then this thesis extracts corporate philanthropy from corporate social responsibility for analysis due to the wide practices among Chinese companies. Both quantitative and qualitative content analyses are employed to investigate the stakeholders and institutions driving philanthropy-disclosure compilations and activities disclosed of 120 leading Chinese multinational corporations in 2017. In a further step, whether or not cash and gift-in-kind giving would in turn benefit Chinese firms’ value are examined based on a sample of Chinese listed companies used in the first chapter, but with the time period extends to 2016.